Determinants of poverty among riverine rural households in Ogun State, Nigeria (2012)
This paper analyzed the poverty status of rural households in Ogun Waterside Local Government Area of Ogun State. Data were collected from 125 households using multistage sampling procedure. Descriptive and Probit regression analytical approaches were used for data analysis. Results show that 28.8 percent of the households were poor. Poverty was perceived to be driven by unemployment, low-investment and neglect by government. Probit results revealed that having farming as primary occupation and household size significantly increased poverty (p<0.10), while amount of credit/loan obtained, educational attainments and monthly expenditure of household significantly reduced it (p<0.10). To alleviate rural poverty, the study concluded that households should have adequate access to affordable and easily accessible credit facilities, among others.